2012
DOI: 10.1155/2012/837495
|View full text |Cite
|
Sign up to set email alerts
|

On Spectrum Sensing for TV White Space in China

Abstract: In the field of wireless communications the idea of cognitive radio is of utmost interest. Due to its advantageous propagation properties, the TV white space can be considered to become the first commercial application of cognitive radio. It allows the usage of secondary communication systems at non-occupied frequency bands. Within this paper, spectrum sensing algorithms are introduced for the three predominant Chinese TV standards DTMB, CMMB, and PAL-D/K. A prototype platform is presented and its underlying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The existing work on white space focused on exploiting the white spaces for broadband access [8,19,20,30,43,54,57,59,[61][62][63][64] and spectrum determination through spectrum sensing [9,26,27,33,48] and/or geo-location database approach [16,18,34,37,63]. Alongside, various standards bodies (e.g., IEEE 802.11af, IEEE 802.15.4m, IEEE 802.19.1, IEEE 802.22, IEEE 1900.4a, IEEE 1900.7, and ECMA-392) and industry leaders (e.g., Microsoft and Google) have also targeted the white spaces for unlicensed personal or commercial use [21,28,43,47]. In contrast, SNOW, as a LPWAN, exploits white spaces for highly scalable and wide-area sensor network applications.…”
Section: Related Workmentioning
confidence: 99%
“…The existing work on white space focused on exploiting the white spaces for broadband access [8,19,20,30,43,54,57,59,[61][62][63][64] and spectrum determination through spectrum sensing [9,26,27,33,48] and/or geo-location database approach [16,18,34,37,63]. Alongside, various standards bodies (e.g., IEEE 802.11af, IEEE 802.15.4m, IEEE 802.19.1, IEEE 802.22, IEEE 1900.4a, IEEE 1900.7, and ECMA-392) and industry leaders (e.g., Microsoft and Google) have also targeted the white spaces for unlicensed personal or commercial use [21,28,43,47]. In contrast, SNOW, as a LPWAN, exploits white spaces for highly scalable and wide-area sensor network applications.…”
Section: Related Workmentioning
confidence: 99%
“…2. A broad review of the general regulatory landscape can be found in [12,35,36], with [12,35] describing the UK, US, and worldwide rules and developments, while [36] gives a brief overview of the various Chinese TV regulation issues.…”
Section: Regulations and Standardisationsmentioning
confidence: 99%
“…The appearance of secondary users may cause significant interference in the TVWS; therefore an advanced spectrum sensing technique is essential. A study about this emerging technology [39] discusses that the sensing threshold is −112.8 dBm for 8 MHz wide channels, showing that high quality sensing technique is inevitable in a real CR application.…”
Section: Mobile Sensing Of the Dvb-t Spectrummentioning
confidence: 99%